(untitled) - Food and Agriculture Organization of the United Nations (Surrey, England, 1972)
The main criterion for the selection of gear designs in this catalogue was proven efficiency in reasonably extensive commercial fishing.
Keywords: Thủy sản,Fisheries,Fishing nets; Thiết bị và sự cung cấp,Thiết kế và xây dựng,Equipment and supplies,Design and construction,Design and construction